2015
DOI: 10.1177/0954406215593773
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics and control of crank–slider mechanism with link flexibility and joint clearance

Abstract: Dynamical behaviors and control of planar crank-slider mechanism considering the effects of joint clearance and link flexibility are studied. A control scheme for maintaining continuous contact is proposed. It was observed that using one actuator for control scheme might cause the actuator to reach its saturation limit, a problem that was bypassed by installing an additional actuator on connecting rod. In one actuator case, only continuous contact can be obtained, while with the aid of two actuators, point con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The results showed that, for maintaining continuous contact in a mechanism with clearance joints, in some cases larger amounts of the input torque may be needed. Again, Yaqubi et al [462,463] introduced a continuous contact constraint equation into the dynamics equations of a planar rigid-slider mechanism with two clearance joints, and derived the required crank control torque to maintain the continuous contact state in the clearance joint. Their numerical results indicated that the continuous contact state could be established.…”
Section: Optimization and Control Of Mechanisms With Clearance Jointsmentioning
confidence: 99%
“…The results showed that, for maintaining continuous contact in a mechanism with clearance joints, in some cases larger amounts of the input torque may be needed. Again, Yaqubi et al [462,463] introduced a continuous contact constraint equation into the dynamics equations of a planar rigid-slider mechanism with two clearance joints, and derived the required crank control torque to maintain the continuous contact state in the clearance joint. Their numerical results indicated that the continuous contact state could be established.…”
Section: Optimization and Control Of Mechanisms With Clearance Jointsmentioning
confidence: 99%
“…sin + = sin (14) With (14), the whole function can be transformed to a one-degree freedom. In this section, equations of motion for a reciprocating compressor are shown in (15), taking into consideration the mass of both the crank and the connecting rod that would otherwise be ignored by many other papers. What is more, the vertical force generated by the deformation of piston rod is also considered since the force has the same magnitude as the horizontal force generated by the piston rod.…”
Section: Equations Of the Model For Reciprocating Compressors Considementioning
confidence: 99%
“…The rigid-flexible hybrid model of mechanism has been studied by many scholars. S. Yaqubi, M. Dardel, and H. M. Daniali [15] studied nonlinear dynamics and control of crank-slider mechanism with link flexibility and joint clearance. Both the case of the mechanism with rigid link and the case with flexible link were studied through simulation and experimental tests [16].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of various noises resulting from the structure (clearance, dimensional, and assembling errors) and dynamic (friction, velocity, and loading) factors is considered in this model. Yaqubi et al 43 studied the dynamical behaviors and control of planar crank-slider mechanism considering the effects of link flexibility and joint clearance. Overall, these researches pointed out the feasibility to reduce the negative effects of clearance joint on the dynamic behavior through modeling.…”
Section: Introductionmentioning
confidence: 99%